Consumer behavior and retail outlet choice for seafood in Zamboanga City, Philippines - Callanta, Daphney Shane A.; Romo, Glory Dee A.; Sarmiento, Jon Marx P.; Alviola, Pedro A., IV (2019)
Zamboanga City is a significant contributor to fish production in the Philippines (16.48%) and particularly in Mindanao (37%). Studies to determine the consumer behavior on this vital commodity have been scarce. This study aims to fill this gap by assessing the different factors that influence consumers' retail outlet choice for seafood. Multinomial logit model was used to assess the retail choice of consumers, namely, supermarket, wet market, and temporary markets (talipapa) using the collected data from 300 respondents. The results showed a higher likelihood of choosing supermarket over retail outlets with higher monthly income, higher educational attainment, and older respondents while belonging to married and male categories decreased this likelihood. Higher budget allocation was shown to increase the likelihood of consumers to choose wet markets over the other retail outlets while higher monthly income had an opposite effect. On the other hand, the higher budget allocation had a negative effect on the consumer's probability in purchasing seafood in talipapa over other retail outlets. While the majority of the respondents preferred to buy seafood in the wet market, this number might dwindle as Zamboanga consumers' income improves and they shift to supermarkets. In addition, majority of the respondents observed an increase in prices of seafood after the implementation of the Tax Reform for Acceleration and Inclusion Act (TRAIN) law. Higher budget allocation for seafood or shift to other alternative foods such as canned goods or noodles were observed after this tax was implemented.
Keywords: Mindanao studies; Seafood industry